'The past is a promise to the future': stories, persons, and the devil in Greece. (30th December 2018) - Tsintjilonis, Dimitri
Abstract: Drawing on ethnography from central Greece, this article is about the way people narrate their encounters with the devil. Although it echoes the idea that life as told and life as lived are structured in the same way, it takes the argument a step further by suggesting they are structured through a narrative plot wherein the present and the future of the story‐tellers pre‐date the past of which their stories tell. It also foregrounds the link between this structure and a particular kind of morality which replicates the narrative logic of the stories, giving rise to an inherently relational personhood – a personhood that, just like the way in which its narration destabilizes the logic of before and after, destabilizes the distinction between self and other. Lastly, contextualizing the current economic crisis in the lives of such persons, the article suggests we need to think of it in relation to the devil and the stories people tell of him.